Digitalization Process by Agricultural Companies, or the Results of a Questionnaire Survey - Szabóné Berta, Olga; Juhász, Csilla (International Journal of Engineering and Management Sciences, 2020)
The term “information society” first appeared in Japanese social science in the early 1960s (Z. Karvalics, 2007). The interpretation of the concept has undergone significant changes over the past decades, showing that dynamically developing societies, which are undergoing constant changes due to the rapid development of information, information management and the dynamism of the digital world. The close relationship and connection between information and information technology has become a fundamental factor in the societies of today, the organizations life, which generates inevitable, sometimes serious debates and profound changes. Economic operators must necessarily be resilient to technological change. We should think of the time of the Industrial Revolution, when modern weaving machines flooded the factories. Otherwise, a resilient organization will not survive in an evolving and ever-changing dynamic economic environment. Of course, this is true of agriculture as well, just as it is for other sectors of the national economy. On the one hand, my assumption on the basis of which my questionnaire was compiled was that enterprise management systems are increasingly used by enterprises in agriculture due to the diversification of activities. At the same time, I assumed that the size of a business could influence the use of information technology (hereinafter IT), so I hoped that my research would provide reliable data on this as well.